2017
DOI: 10.1523/jneurosci.2239-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Focal Seizure Pattern Generated in Superficial Layers of the Olfactory Cortex

Abstract: Seizure patterns identified in focal epilepsies caused by diverse etiologies are likely due to different pathogenic mechanisms. We describe here a novel, region-specific focal seizure pattern that mimics seizure activity observed in a subpopulation of patients submitted to presurgical monitoring with intracerebral electrodes. Distinctive seizure-like events (SLEs) are induced in the olfactory regions by acute treatment of both tangential brain slices and the isolated guinea pig brain with the potassium channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…Recently, we demonstrated a seizure pattern similar to the human P‐type pattern in the olfactory cortex of the isolated guinea pig brain. The onset of this seizure pattern correlated to extracellular potassium changes associated with increased synaptic activity; we proposed that seizure progression involved amplification of potassium release sustained by unmyelinated fiber depolarization . As for the human P pattern, the potassium changes occurring abruptly in the olfactory cortex induce a sharp‐on and sharp‐off potential shift coupled with LVFA.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Recently, we demonstrated a seizure pattern similar to the human P‐type pattern in the olfactory cortex of the isolated guinea pig brain. The onset of this seizure pattern correlated to extracellular potassium changes associated with increased synaptic activity; we proposed that seizure progression involved amplification of potassium release sustained by unmyelinated fiber depolarization . As for the human P pattern, the potassium changes occurring abruptly in the olfactory cortex induce a sharp‐on and sharp‐off potential shift coupled with LVFA.…”
Section: Discussionmentioning
confidence: 90%
“…As for the human P pattern, the potassium changes occurring abruptly in the olfactory cortex induce a sharp‐on and sharp‐off potential shift coupled with LVFA. Interestingly, in the experimental model synaptic transmission is abolished during a P‐type seizure (but not at its onset), possibly because of potassium‐induced fiber depolarization; in principle, this hypothesis could be verified in patients with an appropriate, ethically approved protocol designed for testing the response to low‐amplitude local stimulation of the EZ during P‐type seizures. The ictogenic mechanism proposed for P‐type seizures in the experimental animal model may be relevant to explain seizure generation in focal cortical dysplasia type IIb and in the cortex of TLE patients with and without associated dysplasia, where unmyelinated fibers in the subcortical white matter are pathologically augmented.…”
Section: Discussionmentioning
confidence: 92%
“…We also note that here we have focused on epileptic seizures that show SWDs. We hope to address in the future the case of seizures that do not include ictal SWDs, but remain instead within the dynamics of low-voltage fast-activity oscillations 19 , 28 , 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using the in toto guinea pig brain preparation showed that piriform cortex generates SLEs characterized by fast‐activity on a plateau potential (FAPP). FAPP SLEs are evoked by perfusion with the potassium channel antagonist 4‐AP and are similar to ictal activity seen in patients with frontal neocortical epilepsies . The piriform cortex generates fast activity nested within periodic slow oscillations at 0.1–0.5 Hz that precede the SLE.…”
Section: In Vitro Activity With Relevance To Human Epilepsymentioning
confidence: 85%
“…Activity was recorded with glass capillary electrodes, at 3 KH z sampling in quasi‐ DC mode. (Modified from Avoli et al., 2016 and from Uva et al., 2017. )…”
Section: In Vitro Activity With Relevance To Human Epilepsymentioning
confidence: 99%